LYMPHOCYTIC CHALONES IS A NEW CLASS OF NATURAL ANTIOXIDANTS - Garkava, Kateryna (Proceedings of National Aviation University (archive), 2014)
The analysis of biological properties of lymphocytic chalones, regulators of cell proliferation, indicates the prospect of the creation of these new antioxidant preparations for the correction and normalization of immunological reactions in current adverse conditions of environment.